Road archaeology in the Middle Nile. - Mallinson, M. D. S., (Sudan Archaeological Research Society publication ;, 2017)
Reports on the findings of rescue excavations carried out by SARS in 1994 in advance of the construction of the North Challenge Road, Sudan. The excavation area encompassed from opposite the Pyramids of Meroe to Atbara.